Petrocosmea funingensis (Gesneriaceae): a new species from southeastern Yunnan, China - Zhang, Qiang; Pan, Bo; Meng, Tao; Li, Guo-Feng; Xu, Wei-Bin; Li, Zhi-Ming (Phytotaxa, 2013)
Petrocosmea funingensis, a new species from southeastern Yunnan, China is here described and illustrated. Based on morphological characters it is assumed to belong to section Anisochilus, because of the shallow or slight split of the corolla lobes with the upper lip being nearly half as long as the lower one. Within the section, the new species is associated with the species from series Iodioides, due to the particularly extensive fusion of the two adaxial lobes and is morphologically most similar to P. huanjiangensis and P. iodioides, especially in floral structure and traits, but can be distinguished from these species by several quantitative and qualitative characters of the leaves, peduncles, calices, stamens, staminodes and styles.